Synthesis and Characterization of New Heterocyclic Schiff's Bases from Methyl 4-Hydroxybenzoate. - Abbood, Saja S; Shneine, Jawad K; Ahmed, Ahmed (Al-Nahrain Journal of Science, 2018)
New Schiff's bases with 1,2,4-triazole ring (3a-j) have been synthesized from 4-(4'-amino-5-mercapto-4H-1, 2, 4-triazol-3-yl) phenol (2) which is obtained from 4-hydroxybenzohydrazide (1) by a cyclization reaction. Infrared spectroscopy and 1H NMR spectroscopy were used to characterize the structure of synthesized compounds. All the final products are indicated as keto-enol and thione-thiol tautomers.